2002
DOI: 10.1093/ndt/17.11.1909
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glomerular filtration rate in healthy subjects and normoalbuminuric diabetic patients: validity of a new (MDRD) prediction equation

Abstract: In subjects with a normal or increased GFR, the new MDRD-prediction equation of GFR is less accurate than creatinine clearance or the Cockcroft-Gault formula, and offers no advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
148
4
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(175 citation statements)
references
References 6 publications
13
148
4
10
Order By: Relevance
“…The more recent MDRD equation seems more accurate, but it has not been validated in diabetic kidney disease (10). Its superiority over the Cockcroft-Gault formula has been mentioned in some (14), but not all (15,16), recent reports.…”
mentioning
confidence: 97%
“…The more recent MDRD equation seems more accurate, but it has not been validated in diabetic kidney disease (10). Its superiority over the Cockcroft-Gault formula has been mentioned in some (14), but not all (15,16), recent reports.…”
mentioning
confidence: 97%
“…Validation of the CG and MDRD formulas has been attempted in individuals with known renal disease and normal SCr levels (7), patients with early diabetic nephropathy (8), and individuals without kidney disease (8 -12). However, the different methods used to measure GFR and, more important, the uncertainty about the calibration in SCr measurements limit the interpretation of these results.…”
mentioning
confidence: 99%
“…However, we do not believe this to be a serious limitation of our study as tubular secretion of creatinine is mainly an important contributor to urinary creatinine in subjects with GFR below 25 ml/min per 1.73 m 2 of BSA [17,23] and our subjects had normal or mildly decreased renal function. Furthermore, it has been demonstrated that creatinine clearance is adequate for measuring the GFR when compared to inulin clearance in subjects with normal GFR with or without type 1 diabetes [17].…”
Section: Discussionmentioning
confidence: 89%
“…However, we do not believe this to be a serious limitation of our study as tubular secretion of creatinine is mainly an important contributor to urinary creatinine in subjects with GFR below 25 ml/min per 1.73 m 2 of BSA [17,23] and our subjects had normal or mildly decreased renal function. Furthermore, it has been demonstrated that creatinine clearance is adequate for measuring the GFR when compared to inulin clearance in subjects with normal GFR with or without type 1 diabetes [17]. In Japanese subjects, creatinine clearance is an accepted approach for measuring GFR as it has been demonstrated not only to have an excellent correlation with plasma clearance methods like In-111 DTPA but also to be as accurate as gamma camera methods like Tc-99m DTPA scintigraphy in estimating renal function [24].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation